Sustainable development and environmental management - South East Anatolia project example - Semra Atabay (European Regional Science Association (ERSA), 1998)
The globalization process that leads to the new world order of our times, has an economic and political content in line with the functions undertaken. The global system hinges upon national and international actors as well as the compromise among them. In this framework, environmental problems went far beyond the borders of any country, region and local areas and thus had an impact on the world as a whole, globalizing the responsibilities to a wide extent. Development of agriculture and energy together with demographic growth and environmental problems have rendered international relations important. Economic development is favoring developed countries and putting the developing countries in a more difficult situation than ever. The fact that almost 75% of international trade is among developed countries, constitutes an evidence of the economic difficulties faced by developing countries. It is obvious that abuse of the natural environment in various forms in developed countries for further development and in developing countries only for survival, has a negative impact on sustainable development. On the verge of the year 2000, a common opinion is that the relationship between development and environment can be maintained through policies and implementation tolls. It is claimed that the new economic balance can be harmonized with environmental components without forsaking development. Industrial production receives constant support by giving rise to the need for energy and water which constitutes a global problem. In this context, in order to sustain socio-economic development and improve quality of life, it becomes inevitable to consider natural environment as the sole capital. Therefore, the key to ensure sustainable development and economic viability of environmental resources is to integrate environmental values and costs into economic decisions and policies. In other words, in order to sustain long term socio-economic activities and to ensure an optimum balance, it is necessary to consider the relationship between the relevant industries and natural resources and to measure the maximum capacity. In fact, integration of the environmental dimension to the decision? making mechanisms leads to short and long term strategies for environmental protection. Therefore, considering the ecological and economic decisions in line with the interdependent eco-systems of different countries within the macro space is an important reference step for regional and sector-based planning activities regarding proper and efficient use of natural resources and conservation of vulnerable regions. Such a planning approach is important since ecological space components at the national and international levels within political decision processes influence regional development and investment policies. For this reason, when preparing a national planning policy, ecological and economic principles should be considered with regard to the international space dimension and the necessary legal political framework should be provided for global sustainability. In this context, the South East Anatolia Project introduced for the most underdeveloped region, the south-east of the country - the GAP ? is the largest project concerning water and energy resources in a developing country, Turkey. Within this project, an integrated and coordinated program and planning activities are foreseen in the region regarding agriculture, industry, education, health, infrastructure, transportation and communication. As it is known, with its international river basins, forests and soils, the South East Anatolia region is quite a vulnerable region regarding ecological and political components. This paper discusses the realization of international cooperation and monitoring activities regarding trans-border natural resource management and regional and sub-regional plan in light of the GAP Project.
Keywords: 330